The Effect of Progressive Muscle Relaxation on Low Back Pain And Anxiety in Primiparas - Diah Evawanna Anuhgera; Nikma Jalilah; Riris Sitorus; Dwi Handayani; Debi Dinha Octora (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Pregnancy changes that result in looseness and instability of joints in the third trimester of pregnancy often cause lower back pain in mothers. This certainly disturbs the mother's discomfort and causes anxiety. Progressive muscle relaxation is a combination of deep breathing and progressive muscle relaxation techniques by stretching and relaxing the muscles systematically. The purpose of this study was to analyze the effect of progressive muscle relaxation on lower back pain and anxiety in primigravida pregnancies. This study used all experiments with a pretest-posttest controlled group design for primigravida pregnant women with a gestational age of 28-36 weeks at the Misriah Galang Clinic as many as 28 respondents. The sampling technique used was simple random sampling. There were two groups in this study, namely the intervention group with progressive muscle relaxation and the control group. The research instruments used were VAS (Visual Analog Scale), Hamilton Anxiety Rating Scale (HARS) and questionnaires. Data analysis used was the dependent t-test and independent t-test to measure pain intensity and the Wilcoxon test with Mann Whitney to measure anxiety. There was a difference in the intensity of pain and anxiety before and after the progressive muscle relaxation intervention with a value of p = 0.001 and 0.004. The percentage of pain reduction after the intervention was 45.71%. There was a difference in the average pain and anxiety after the intervention between the control and intervention groups with a value of p = 0.000; p = 0.002. Progressive muscle relaxation has been proven effective in reducing the intensity of lower back pain and anxiety. Obstetric practitioners can apply this method to pregnant women who experience lower back pain and anxiety. The progressive muscle relaxation method can be used as material in Complementary Therapy in Pregnancy to develop obstetric science.